Programs for Aspiring Principals: Who Participates? Issue Brief - De Angelis, Karen; Rossi, Robert; American Institutes for Research in the Behavioral Sciences, Washington, DC. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
Recommendations for reform of principal-preparation programs identify schools and school districts as important agents in the principal-preparation process. In the 1993-94 Schools and Staffing Survey (SASS), conducted by the National Center for Education Statistics (NCES), public school principals indicated whether or not they had formerly participated in any district or school training program for aspiring school principals. This brief presents the percentages of public school principals--overall, by sex and minority status, and by school locale and level--who reported having taken part in such programs. The brief also compares the participation rates of new principals (those with fewer than 4 years of experience) with the participation rates of more experienced principals (those with 4 or more years of experience). Findings indicate that in 1993-94, nearly one-half of new principals had participated in a school or district aspiring-principals program. Overall, greater percentages of female than male principals participated in aspiring-principals programs. More than half of all minority principals had taken part in such programs. Overall, participating principals were most likely to work in elementary central-city and urban-fringe schools than in secondary, rural schools. In general, new principals reported higher levels of participation in aspiring-principals programs than experienced principals. Two tables are included. (LMI)
Availability: Internet: http://www.ed.gov/NCES.
Sponsoring Agency: National Center for Education Statistics (ED), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Elementary Secondary Education; Leadership Training; Minority Groups; Principals; Professional Development; Public Administration Education; Public Schools; Sex; Urban Schools; Beginning Principals; Information Analyses